Engraftment of Insulin-Producing Cells from Porcine Islets in Non-Immune-Suppressed Rats or Nonhuman Primates Transplanted Previously with Embryonic Pig Pancreas - Marc R. Hammerman (Journal of Transplantation)
Transplantation therapy for diabetes is limited by unavailability of donor organs and outcomes complicated by immunosuppressive drug toxicity. Xenotransplantation is a strategy to overcome supply problems. Implantation of tissue obtained early during embryogenesis is a way to reduce transplant immunogenicity. Insulin-producing cells originating from embryonic pig pancreas obtained very early following pancreatic primordium formation (embryonic day 28 (E28)) engraft long-term in non-immune, suppressed diabetic rats or rhesus macaques. Morphologically, similar cells originating from adult porcine islets of Langerhans (islets) engraft in non-immune-suppressed rats or rhesus macaques previously transplanted with E28 pig pancreatic primordia. Our data are consistent with induction of tolerance to an endocrine cell component of porcine islets induced by previous transplantation of embryonic pig pancreas, a novel finding we designate organogenetic tolerance. The potential exists for its use to enable the use of pigs as islet cell donors for humans with no immune suppression requirement.